A LITERARY ANALYSIS OF NGWABA’S ‘GOD’S NEVER REGRETTED’ - MAZONO Manassé & MUJINGA Nathalie Biselela (Ziglôbitha)
Abstract: Literature is produced by implied writers and it is addressed to implied authors. To understand a piece of literature people should analyze it deeply. Thus, the authors of this article try to provide a literary analysis of Ngwaba’s poem “God’s Never Regretted”.  Their aim is to sort out and explain the important messages the poet intends to transmit to his readers.